Comparative Analysis of Mortality from Infectious Diseases in the Russian Federation and Some European Countries - R. V. Polibin; A. Ya. Mindlina; A. A. Gerasimov; N. I. Briko (Эпидемиология и вакцинопрофилактика, 2017)
The purpose. To conduct comparative evaluation of mortality from infectious diseases and medical care quality in Russia and some European countries in different age groups. Materials and methods. Selection of mortality data was performed from various Russian and foreign databases. Ranking of countries according to mortality rates was done with a quartiles calculation method. For evaluating the adherence to preventive measures surveys of different population groups, to assess adherence to the principles of clinical epidemiology and evidence-based medicine was conducted a continuous survey of doctors, one branch of the municipal polyclinic of Moscow. The results and discussion. It is shown that the situation in the Russian Federation as a whole can be assessed as disadvantaged in mortality from infectious diseases in all age groups. Conclusions. A reduction in mortality among children as well as working-age population requires a comprehensive approach that should include both of improvement of quality of care and the formation of commitment to preventive measures.